(3CRgGQ GdCacGQ aj LhGgQ GdCMLGQs - (3GdJjaGTj , CMeO Hf jhSa Hf CMeO Hf CHj HcQ Hf MeOhf GdbjSj, TQa GdOjf,J (B651 (3g` s
(3BNQgG (B:s
(3JfJgi HGdHGH GdYGTQ s
(3fSNI KGfjIs
(3jdGMX Cf gPG GdcJGH gh cJGH GdGMLGQ GdedhcjI ai JQJjHg hYOO GdCMLGQ GdehUhaI ajg eY JZjjQ ai GdOjHGLI hHYV GdYHGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B273 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B208s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B7 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B72s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs